T2 mapping provides multiple approaches for the characterization of muscle involvement in neuromuscular diseases: a cross‐sectional study of lower leg muscles in 5–15‐year‐old boys with Duchenne muscular dystrophy. (9th October 2012) - Arpan, Ishu; Forbes, Sean C.; Lott, Donovan J.; Senesac, Claudia R.; Daniels, Michael J.; Triplett, William T.; Deol, Jasjit K.; Sweeney, H. Lee; Walter, Glenn A.; Vandenborne, Krista
<x xml:space="preserve">Abstract</x> Skeletal muscles of children with Duchenne muscular dystrophy (DMD) show enhanced susceptibility to damage and progressive lipid infiltration, which contribute to an increase in the MR proton transverse relaxation time (T2). Therefore, the examination of T2 changes in individual muscles may be useful for the monitoring of disease progression in DMD. In this study, we used the mean T2, percentage of elevated pixels and T2 heterogeneity to assess changes in the composition of dystrophic muscles. In addition, we used fat saturation to distinguish T2 changes caused by edema and inflammation from fat infiltration in muscles. Thirty subjects with DMD and 15 age‐matched controls underwent T2‐weighted imaging of their lower leg using a 3‐T MR system. T2 maps were developed and four lower leg muscles were manually traced (soleus, medial gastrocnemius, peroneal and tibialis anterior). The mean T2 of the traced regions of interest, width of the T2 histograms and percentage of elevated pixels were calculated. We found that, even in young children with DMD, lower leg muscles showed elevated mean T2, were more heterogeneous and had a greater percentage of elevated pixels than in controls. T2 measures decreased with fat saturation, but were still higher (P < 0.05) in dystrophic muscles than in controls. Further, T2 measures showed positive correlations with timed functional tests (r = 0.23–0.79). The elevated T2 measures with and without fat saturation at all ages of DMD examined (5–15 years) compared with unaffected controls indicate that the dystrophic muscles have increased regions of damage, edema and fat infiltration. This study shows that T2 mapping provides multiple approaches that can be used effectively to characterize muscle tissue in children with DMD, even in the early stages of the disease. Therefore, T2 mapping may prove to be clinically useful in the monitoring of muscle changes caused by the disease process or by therapeutic interventions in DMD. Copyright © 2012 John Wiley & Sons, Ltd.